A numerical method for studying Hoof bifurcation of plane Poiseuille flow - Tran, Tran Van (Vietnam Journal of Mechanics, 1993)
The Hoof bifurcation of plane Poiseuille flows is studied numerically. On the base of the rigorous theory worked out by Joseph and Stringer [1], a detailed effective and simple algorithm for numerical determination of the type of the above mentioned bifurcation is proposed. The obtained result shows that the bifurcation at the lower branch of the linear stability neutral curve is supercritical meantime at the upper branch the one is subscritical.